ANALISIS PENGARUH KEGIATAN DIVISI JASA KEAGENAN KAPAL DAN PENGGUNAAN BAHAN BAKAR KAPAL DALAM MENINGKATKAN PENDAPATAN PERUSAHAAN - Puri Rohmatulloh (The Asia Pacific Journal Of Management Studies, 2022)
PT. Pertamina (Persero) Jakarta is a head company that move in Oil & Gas petrolium industry and Non Oil and Gas Petrolium Industry. The core bussiness Pertamina activity is exporting and distributing fuels to Indonesia archipelago are operated by many kind of ship from Pertamina. Based on the result data from division Ship agency service it’s indicated there is Pertamina organization transformation from time to time, human resources issue and working culture as well as environmental change of bussiness resulted in less potential income through Division of PT. Pertamina Ship Agency.This research aimed at analyzing the effect of ship service agency division activity and the ship fuel consumption in increasing the company income of PT Pertmina (Persero) in Jakarta. The reseach method the used by the Researcher is descriptive qualitative, the data is obtained from the result of SWOT Analysis by using IFAS and EFAS approach. The result research is finded that Division of Pertamina Service Agency activity showed Strength solid organization environment in Ship Division of PT. Pertamina (Persero) with less effecting influence on Pertamina Shipping Department by the weakness this metter is graetly beneficial for the development of service agency division in taking the opportunity to face threat external of PT Pertamina in shipping departement, even Pertamina Ship Fuel Consumption has showed significant strength solid in Pertamina (Persero) Organization in shipping departement with less effecting influence on Pertamina Shipping Departement. This matter is graetly benefecial for the efficincy ship fuel consumption in taking opportunity to face external environment PT. Pertamina (Persero) threat in shipping departement. In order to good ship service agency division activity and eficincy the shipping fuel consumption in increasing the company income of PT Pertmina (Persero) in Jakarta.